CURRENT STATE OF FORMATION OF LIFE-CREATIVE ABILITIES OF SENIOR PUPILS - Kyrychenko, Valentyna; Yezhova, Olha (Theoretical and Methodical Problems of Children and Youth Education, 2024)
The lives of modern Ukrainian high school students are characterised by extreme instability of security and socio-psychological factors. This requires the Ukrainian education system to develop effective tools for building resilience, vitality and life creativity as a prerequisite for preserving their health and life. Hence, the awakening and development of their life-creative abilities become the value and semantic guidelines of the educational component of the educational process during the war. The purpose of the article is to determine the current state of development of life-creating abilities of senior pupils of institutions of general secondary education to take into account their characteristics in the further development of the educational program of the institution for the formation of life success of senior pupils. Achieving the set goal involves the following tasks: to determine the level of formation of life-creating abilities of senior pupils of experimental educational institutions; to carry out factor and cluster analyzes and, according to their results, organize the comparative characteristics of selected groups of respondents; to formulate research conclusions and recommendations regarding the development of life-creating abilities of senior pupils in the conditions of a mixed form of organization of the educational process. The diagnostic base was made up of theoretical and empirical research methods. The article presents the results of the study of the current state of life-creative abilities of senior pupils, carried out by scientists of the Laboratory of Physical Development and Healthy Lifestyle of the Institute of Problems on Education of the National Academy of Educational Sciences of Ukraine within the framework of the research “Formation of Life Success of Senior Pupils in the Post-War Reality”. The questionnaire “Life-Creating Abilities” developed by A. Bolshakova was chosen as an empirical method to determine the current state of the life-creating abilities of senior pupils. Based on the factor and cluster analysis of the obtained scientific results, 3 groups of life-creative abilities of senior pupils (with insufficient, medium, and high levels of development) have been identified. Most senior pupils (42% of the total respondents) have an average level of development of life-creating abilities, 30% have a high level, and 28% have an insufficient level. The proposals for taking into account differences in the levels of life-creative abilities in the development of the educational program of an educational institution are substantiated. Among the educational technologies, it is proposed to give preference to those that instrumentalize life design (SWOT, SNW, PDCA analysis methods, portfolio technologies, reflective-explicit method, creolized texts, and digital tools for their implementation).